Freshwater Crustacean Zooplankton of Europe Cladocera & Copepoda (Calanoida, Cyclopoida) Key to species identification, with notes on ecology, distribution, methods and introduction to data analysis - Bledzki, Leszek A.; Rybak, Jan Igor (Springer International Publishing : Imprint: Springer, 2016)
This work provides a user-friendly, species level taxonomic key based on morphology, current nomenclature, and modern taxonomy using molecular tools which fulfill the most pressing needs of both researchers and environmental managers. This key arms the reader with the tools necessary to improve their species identification abilities. This book resolves another issue as well: the mix of female and male characters used in keys to the calanoid copepods. Often, during the identification process, both calanoid copepod sexes are not available, and the user of such a key is stuck with an uncertain identification. Here, separate male and female keys to the calanoid copepods are provided for both the genera and species levels.